Exploration of Unggan weaving in Minang culture: An ethnomathematics study - Kusno; Yolanda, Gelvia; Supiyati, Sri (Universitas Hamzanwadi, 2024)
Unggan weaving, an original cultural product of the Sijunjung people, especially in Unggan Village, is widely used as employee, traditional, and school uniforms once a week. However, the use of Unggan weaving in mathematics learning has yet to be widely explored. This research aims to reveal the mathematical elements of Unggan weaving as a learning vehicle more appropriate to students' culture. This research is qualitative research with an ethnographic approach. Data collection methods use in-depth interviews, documentation, and ethnographic notes. The interview subjects were Ernita, owner of Unggan Weaving (R-1), and Masniati, an employee of Unggan Weaving (R-2). Data analysis uses the results of interpretation and translation of the phenomena found, as well as based on the results of the informant's conception of the meaning and the informant's original language regarding the focus, which is combined verbally with the researcher's language after in-depth understanding through focus group discussions (FGD). The research results show that Unggan woven fabric contains mathematical elements of geometric transformation (translation, reflection, dilation, symmetry) and arithmetic number patterns. The results of this research can be recommended as material for developing school mathematics teaching materials based on local wisdom.